A Story of Failed Conversions: The Impossible Refashioning of Tradition in Benito Pérez Galdós's Rosalía. Issue 4 (1st October 2020) - Useche, Óscar Iván
Abstract: The tragic ending of the protagonists in Benito Pérez Galdós's unfinished novel, Rosalía, exposes the multiple anxieties that economic and technological development produced in Spain at the end of the nineteenth century. The story reveals the symbolic conflict that emerged from the ideological attempt to refashion the past and make it an organic part of the country's modernization. I show how the text's negative representations of the trope of conversion—from Protestantism to Catholicism, from landed wealth to finance capital, and from aristocratic authority to bureaucratized power structures—are projections of the uncertainties and fears brought about by material progress. By incorporating train travel and the stock market as the plot's turning points, Galdós presents two incompatible visions of the world that come into sight in the contrast between England and Spain, thus uncovering the ideological gap between the society of the time and the progressive nation liberals imagined in the future.